Patient Satisfaction and Loyalty Based on Servqual and PRP Dimensions at the Dental Polyclinic of Sragen Hospital - Erdianto Setya Wardhana; Irma Dewi Ratnawati; Novtania Zahira Shafira (Indonesian Journal of Dentistry, 2026)
Background: Dental and oral health is part of overall health, and one aspect of dental and oral health services is the presence of a dental and oral polyclinic in a hospital. Good health services pay attention to aspects of service quality, consisting of reliability, responsiveness, guarantees, tangible evidence, and empathy.Objectives: This study aims to determine the influence of service quality on patient satisfaction at the dental polyclinic of dr. Soehadi Prijonegoro Hospital, Sragen Regency.Methods: This study uses a concurrent method and a purposive sampling technique with 41 samples. The research variables included the independent variable of service quality and the dependent variable of patient satisfaction levels. The research instrument used was a questionnaire and interview guidelines. Data analysis included validity and reliability tests, as well as Spearman correlation and ordinal regression tests.Outcome: The results of this study showed that the validity and reliability tests had an interval of 0.329, and all items were declared valid. The correlation between service quality and patient satisfaction at dr. Soehadi Prijonegoro Hospital, Sragen Regency, showed a lowest coefficient value of 0.466 and a highest of 0.587. Service quality simultaneously affects patient satisfaction by 99.8%.Conclusion: Based on the results of the study, it was concluded that dental and oral polyclinic patients were very satisfied with the quality of services provided by doctors and nurses at dr. Soehadi Prijonegoro Hospital, Sragen Regency.